MAIN FEATURES OF CREATING A DEMOCRATIC STATE AND CIVIL SOCIETY IN UZBEKISTAN - Uralov Dilshodbek; Habibjonov Izzatbek (Western European Studies, 2025)
This article analyzes the foundations of the creation of a democratic state and civil society: legal foundations, criteria, necessity and prospects. Theoretical and legal consideration of the structure of civil society in the Republic of Uzbekistan. Based on reading this article, the reader will come to the conclusion about the need to manage civil society and the rule of law as an organ of the world community.
Keywords: democracy; law; freedom; citizenship